Excessive Neutrophils and Neutrophil Extracellular Traps in COVID-19 - Wang, Jun; Li, Qian; Yin, Yongmei; Zhang, Yingying; Cao, Yingying; Lin, Xiaoming; Huang, Lihua; Hoffmann, Daniel; Lu, Mengji; Qiu, Yuanwang (Frontiers in Immunology, 2020)
Background: Cases of excessive neutrophil counts in the blood in severe coronavirus disease (COVID-19) patients have drawn significant attention. Neutrophil infiltration was also noted on the pathological findings from autopsy. It is urgent to clarify the pathogenesis of neutrophils leading to severe pneumonia in COVID-19. Methods: A retrospective analysis was performed on 55 COVID-19 patients classified as mild (n = 22), moderate (n = 25), and severe (n = 8) according to the Guidelines released by the National Health Commission of China. Trends relating leukocyte counts and lung estimated by chest CT scan, were quantified by Bayesian inference. Transcriptional signatures of host immune cells of four COVID19 patients were analysed by RNA sequencing of lung specimens and BALF. Results: Neutrophilia occurred in 6 of 8 severe patients at 7 to 19 days after symptom onset, coinciding with lesion progression. Increasing neutrophil counts paralleled lesion CT values (slope: 0·8, 0·3-1·2), reflecting neutrophilia-induced lung injury in severe patients. Transcriptome analysis revealed that neutrophil activation was correlated with 17 neutrophil extracellular traps (NETs) associated genes in COVID-19 patients, which related with innate immunity and interacted with T/NK /B cells, as supported by protein-protein interaction network analysis. Conclusion: Excessive neutrophils and associated NETs could explain pathogenesis of lung injury in COVID-19 pneumonia.